Towards Added Value Attieke Production in Côte d’Ivoire Using Bacillus spp. as Starters - Charlotte Ayawovi Ehon; Regina Krabi; Antoine Assamoi; Sébastien Niamké (Turkish Journal of Agriculture: Food Science and Technology)
In Côte d’Ivoire, the most fermented cassava food product is “attiéké”. Various microorganisms involved in this fermentation process. Bacillus spp. are well-known for their multi-potential enzymatic activities. In this study, Bacillus spp. strains were studied for their ability of growing in environmental stress as follow: NaCl (2 to 9%) and lactic acid (0.1 to 1%). The growth of the studied strains was inhibited at 5% (1 strain), 7% (2 strains) and 8% (7 strains) for NaCl and beyond 0.25% for lactic acid. The ability of the isolated Bacillus strains to ferment cassava dough for “attiéké” production was also tested. The results of sensory tests showed that “attiéké” produced with Bacillus spp. strains was quite similar to “attiéké” control (traditional “attiéké”) except for the brilliance and granulation for which the control obtained the highest scores. The present research indicated that cassava dough fermentation, initiated by the inoculation of Bacillus strains associated with or without lactic acid bacteria should be useful to improve and standardize the quality of “attiéké” produced in Côte d’Ivoire.